The Comparison of Physical Fitness, Anthropometric Characteristics, and Visual Acuity of Goalball Players with Their Right Shot Performance. (November 2020) - Kimyon, Bulent; Ince, Gonca
Introduction: This study investigated the relationship between physical fitness, anthropometric characteristics, visual acuity of athletes with visual impairments, and their right shot performance. Method: The participants of the study involved 34 male athletes with different visual acuities who participated in the 2015 Visually Impaired Schools Goalball Championship in Alanya, Turkey. The means of the participants' age, body weight, height, and sport age were 14.95 ± 1.28 years, 52.06 ± 8.89 kilograms, 163.58 ± 10.39 centimeters, 02.39 ± 1.50 years, respectively. The participants' physical fitness, body fat percentage, handgrip (right–left), and spine flexibility were measured. Upper and lower extremity lengths were obtained through anthropometric measurements, and the athletes' right shot performance was calculated. To analyze the data, the Shapiro–Wilk test was used, and one-way analysis of variance and independent sample t- test were performed, because the data showed a normal distribution ( p = .106). In addition, multivariate regression model analysis was utilized to investigate the relationship between all parameters and the athletes' right shot performance. Results: A significant difference was found among the groups' right shot performance ( p = .03), specifically on behalf of the athletes with low vision. When the participants' anthropometric features, physical fitness values, and their right shot performance were examined, a positive relationship was observed between their dominant (right) handgrip strength and right shot performance (stepwise method; p = .03, R 2 = 0.14). However, no significant difference emerged between their anthropometric characteristics and right shot performance. Discussion: It is considered that visual acuity and upper extremity muscle strength are of vital importance in goalball. Implications for practitioners: Whereas the International Blind Sports Federation applies rules according to visual acuity to offer equal conditions for some areas of sport, in goalball such a rule does not exist. It is important to make a change in the regulations for competition groupings according to visual acuities in goalball like in other sports for individuals with visual impairments. More frequent workout oriented to upper extremity muscle strength during right shot performance is suggested in the training sessions.